Energy-efficient certificateless signcryption for secure data transfer in wireless sensor networks - Paruvathavardhini Jaganthan; Sargunam Balusamy (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2025)
Wireless sensor networks (WSN) have gained high popularity in the realm of technological innovation and have a prime responsibility of transferring the data safely to the sink despite the vulnerable situation presiding around the network. There needs to be a compromise made between energy consumption and the intricate network security system because they are inversely correlated. To create a safe and effective data transfer between the communicating nodes, a new censored regressive jaccard indexed certificateless signcryption (CEJICS) technique is suggested. Initially, the Gaussian likelihood censored regression is applied to identify the energy efficient node which supports enhancing the network lifetime. The security is implemented using the rabin cryptographic jaccard indexive certificateless signcryption (RCJICS). To create a signcryption system with the characteristics of digital signature and ciphertext authenticity, the proposed work focuses on certificateless cryptography. The NS-2 simulator is used for the simulation, and performance metrics are used to evaluate it. According to the observed quantitative results, the suggested CEJICS method outperforms the other conventional methods by improving the packet delivery ratio (PDR) by 93%, achieving a minimum drop of 7%, reducing delay by 22%, reducing overhead to 17%, minimizing energy consumption by 15%, and ultimately extending the network lifetime by 10%.